2015
DOI: 10.1038/hr.2015.3
|View full text |Cite
|
Sign up to set email alerts
|

Add-on effect of hydrochlorothiazide 12.5 mg in Japanese subjects with essential hypertension uncontrolled with losartan 50 mg and amlodipine 5 mg

Abstract: This study assessed the antihypertensive efficacy of a triple combination, fixed-dose therapy of losartan 50 mg (L50)/hydrochlorothiazide 12.5 mg (H12.5)/amlodipine 5 mg (A5) versus co-administration of L50 plus A5 (L50+A5) in Japanese subjects with uncontrolled essential hypertension. Initially, all subjects received single-blind treatment with L50+A5 for 8 weeks. Subjects whose blood pressure (BP) remained stable within pre-specified limits during the last 4 weeks of L50+A5 administration were randomized (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The participants in their trial had a significantly reduced DBP and SBP compared with baseline levels after 30, 60 and 120 days of treatment. 13, 14 In addition, as a result of the add-on effect of hydrochlorothiazide in a short-term study, Rakugi et al 15 found that treatment with 50 mg losartan+12.5 mg hydrochlorothiazide+5 mg amlodipine for 8 weeks did not result in a significant difference in DBP reduction but did show a significant difference in SBP reduction compared with 50 mg losartan+5 mg amlodipine.…”
Section: Discussionmentioning
confidence: 99%
“…The participants in their trial had a significantly reduced DBP and SBP compared with baseline levels after 30, 60 and 120 days of treatment. 13, 14 In addition, as a result of the add-on effect of hydrochlorothiazide in a short-term study, Rakugi et al 15 found that treatment with 50 mg losartan+12.5 mg hydrochlorothiazide+5 mg amlodipine for 8 weeks did not result in a significant difference in DBP reduction but did show a significant difference in SBP reduction compared with 50 mg losartan+5 mg amlodipine.…”
Section: Discussionmentioning
confidence: 99%
“…Post hoc sensitivity analyses using alternative methods for zero-cell correction and heterogeneity estimation were conducted according to previous recommendations. (32,(39)(40)(41)(42)(43) Publication bias was assessed by visual analysis of funnel plots and computation Ando (54) 2009 ONEAST (Japan) Genthon (56) 1994 (multinational) Giles (51,95) 1992 (USA) Kario (57,96) 2017 NOCTURNE (Japan) Kato (58) 2011 MOTHER (Japan) Lonn (61,97) 2016 Merck (74,98,99) 2010 Novartis (72,102,103) 2008 ACQUIRE (multinational) Perez-Castrillon (52) 2003 (Spain) Puttnam (11,26,109) 2017 ALLHAT (multinational) Rakugi (64,110) 2015 (Japan) Raveau-Landon (65) 1991 (France) Reid (47,111) 2000 (New Rodgers (66,112) 2011 (53,115,116) 1991 SHEP (multinational) Weidler (68) 1995 Yamada (70) 1989 (Japan) of Egger and Begg tests for outcomes with more than 10 studies. (44)(45)(46) Results…”
Section: Heterogeneity and Publication Biasmentioning
confidence: 99%
“…The other nine trials [20][21][22][23][24][25][26][27][28] including a total of 3307 participants, had a variable 4 to 8 weeks pre-randomisation run-in on sub-maximal dual therapy, in all but one trial [20], before randomisation to either triple therapy (with the addition of an extra drug) or continued dual therapy.…”
Section: Characteristics Of Included Trialsmentioning
confidence: 99%
“…Goal BP levels to define BP control were similar across trials: <140 & <90 in seven trials [16][17][18][21][22][23][24], <140 & <90 or (<130 & <80 in those with diabetes and/or kidney disease) in five trials [15,19,20,27,28], DBP <90 or ≥10 mmHg reduction in DBP from baseline in two trials [25,26].…”
Section: Characteristics Of Included Trialsmentioning
confidence: 99%